Esthetic patient satisfaction, marginal bone loss and peri-implant tissue success in esthetic zone: systematic review - Bushra, Sherif; Khierla, Lamiaa; El Guindy, Jylan; Fahmy, Nadia; El Nahass, Hani (Brazilian Dental Science, 2022)
Increased patient demands for highly esthetic implant superstructure in the anterior esthetic zone has increased in the last decades. Moreover, the absence of periodontal ligament in implant supported prosthesis causes forces to be transferred without cushioning effect to the alveolar bone, resulting in increased marginal bone loss (MBL) and influence the heath of peri-implant tissue. Evaluate the available evidence on the effect implant superstructure and it consequences on patient satisfaction, MBL, bleeding on probing (BOP) and probing depth (PD). A protocol of electronic and hand research was performed for English based researches comparing implants inserted in the esthetic zone with all ceramic superstructure: “Will the use of different types of all ceramic superstructure show different esthetic patient satisfaction, marginal bone loss, bleeding on probing and probing depth? Thirteen publications from one thousand one hundred and sixteen research studies were included. This systematic review showed that all ceramic implant superstructure was a versatile treatment option with higher esthetic patient satisfaction and better color of peri-implant mucous especially in patients having thin biotype. On the other hand there wasn’t significant difference in MBL, PD and BOP compared to other conventional implant superstructure. More randomized controlled clinical trials with bigger samples are needed to confirm our findings. All ceramic implant superstructure is versatile and highly esthetic treatment option for implant placed in the anterior esthetic zone. KEYWORDS Esthetic; Patient satisfaction; Tissue success; Marginal bone loss; Superstructure.